Influence of yeast on the yield of fermentation and volatile profile of 'Węgierka Zwykła' plum distillates. Issue 4 (28th October 2016) - Pielech‐Przybylska, Katarzyna; Balcerek, Maria; Nowak, Agnieszka; Patelski, Piotr; Dziekońska‐Kubczak, Urszula
Abstract : The character of plum brandies depends on a unique aroma profile of the plum and the microbiota present on the surface of the fruits, as well as yeast used for fermentation. In this study, an evaluation of the effect of microorganisms applied for the fermentation of Węgierka Zwykła var. plum mashes and processing temperature (18 °C, 30 °C) on its efficiency and volatile profile, as well as taste and flavour of distillates obtained was performed. An estimation of the odour activity values (OAVs) of the volatile compounds was also conducted. Regardless of whether the fermentation was carried out using Saccharomyces bayanus wine yeast or by native microflora present on plums as well as raisins, the efficiency of this process was high and ranged between 91.7 and 96.7% of the theoretical efficiency. Especially rich in esters (among others ethyl acetate and isoamyl acetate) was the distillate derived after fermentation with the microflora of plums and raisins, at 18 °C. An evaluation of the individual aromatic effect of chemical compounds present in tested distillates, in terms of their OAVs, revealed that the highest OAVs were reached with isovaleraldehyde. Other compounds that showed aroma values >1 and possibly had an effect on the overall aroma of tested plum distillates were the following: hexanal, benzaldehyde, ethyl acetate, isoamyl acetate, ethyl benzoate, ethyl hexanoate, 1‐propanol, 2‐methyl‐1‐butanol, 3‐methyl‐1‐butanol and 1‐hexanol. The performed sensory ranking showed that the best rated distillate was the one obtained after fermentation with the indigenous microflora of plums and raisins, at 18 °C. Copyright © 2016 The Institute of Brewing & Distilling